2013
DOI: 10.1152/ajpcell.00031.2013
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-d-aspartate receptors in human erythroid precursor cells and in circulating red blood cells contribute to the intracellular calcium regulation

Abstract: The presence of N-methyl-D-aspartate receptor (NMDAR) was previously shown in rat red blood cells (RBCs) and in a UT-7/Epo human myeloid cell line differentiating into erythroid lineage. Here we have characterized the subunit composition of the NMDAR and monitored its function during human erythropoiesis and in circulating RBCs. Expression of the NMDARs subunits was assessed in erythroid progenitors during ex vivo erythropoiesis and in circulating human RBCs using quantitative PCR and flow cytometry. Receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 77 publications
(82 reference statements)
3
92
0
1
Order By: Relevance
“…However, expression of mRNAs in different tissues surprisingly revealed that genes encoding for ligand-gated ion channels are not exclusively expressed in neurons but can also be expressed in many other cell types. As an example, NMDA receptors are also expressed in red blood cells (Makhro et al, 2013). However, when considering biologic questions from a broader perspective, it became obvious that cells from different tissues might exploit the vast repertoire of membrane proteins encoded in the genome.…”
Section: F Nonneuronal Related Diseasesmentioning
confidence: 99%
“…However, expression of mRNAs in different tissues surprisingly revealed that genes encoding for ligand-gated ion channels are not exclusively expressed in neurons but can also be expressed in many other cell types. As an example, NMDA receptors are also expressed in red blood cells (Makhro et al, 2013). However, when considering biologic questions from a broader perspective, it became obvious that cells from different tissues might exploit the vast repertoire of membrane proteins encoded in the genome.…”
Section: F Nonneuronal Related Diseasesmentioning
confidence: 99%
“…This strongly indicates the presence of multiple Ca 2+ uptake pathways in EPCs during differentiation (52). We have recently reported the presence of N -methyl- d -aspartate receptors (NMDARs) in human progenitor cells and have shown that these nonselective, ligand-gated cation channels mediate Ca 2+ uptake in EPCs (18, 35). …”
mentioning
confidence: 99%
“…Indeed, these receptors have been reported in a variety of cells and tissues, including osteoclasts, megakaryocytes, leucocytes, and RBCs (28, 35, 37, 39, 41). NMDARs are formed of glycine-binding subunits GluN1 and GluN3A/3B, and glutamate-binding subunits GluN2A/2B/2C/2D (12, 46, 59).…”
mentioning
confidence: 99%
“…We have shown that subunit composition of cardiac NMDARs differs substantially from that in the brain (50) and resembles that in erythroid precursors and red cells (51). Mapping of the NMDAR subunits expression pattern within the heart chambers revealed that cardiac receptors formed by the GluN3A-GluN2D/2B with lower abundance of GluN1, 2A and 2C that are present at low levels in certain areas of the heart only ( Table 3).…”
Section: Characterization Of Cardiac Nmdarsmentioning
confidence: 83%